1991
DOI: 10.1002/bms.1200201210
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of animal blood samples after fragrance drug inhalation by gas chromatography/mass spectrometry with chemical ionization and selected ion monitoring

Abstract: The fragrance compounds linalool (1) and linalyl acetate (2) could be detected, identified and quantified (1: 7-9 ng ml-1; and 2: 1-2 ng ml-1 and 4-5 ng ml-1 as free linalool) in blood samples after inhalation in animal experiments (mice) by gas chromatography/mass spectrometry (GC/MS) with chemical ionization (CI) (ammonia); selected ion monitoring (SIM) mode (1: m/z 81, 137 and 154; 2: 47, 57 and 137) and GC/flame ionization detection (FID). The inhalation of these monoterpenes in concentrations of 5 mg l-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Psychopharmacological in vivo evaluation has shown that linalool possesses dose-dependent marked sedative effects at the CNS including hypnotic, anticonvulsant and hypothermic properties (Jirovetz et al, 1991). This evidence suggests that linalool may take account of at least some of the behavioral effects of Salvia elegans.…”
Section: Discussionmentioning
confidence: 98%
“…Psychopharmacological in vivo evaluation has shown that linalool possesses dose-dependent marked sedative effects at the CNS including hypnotic, anticonvulsant and hypothermic properties (Jirovetz et al, 1991). This evidence suggests that linalool may take account of at least some of the behavioral effects of Salvia elegans.…”
Section: Discussionmentioning
confidence: 98%
“…The motility of mice that inhaled linalool (a compound found in lavender) decreased 40%. 43 Even stimulation with caffeine did not return activity to normal levels.…”
Section: Neurologicalmentioning
confidence: 96%
“…10) Linalool, a monoterpene compound that is reportedly a major volatile component of the essential oils of several aromatic species, is used in traditional medicine systems to relieve symptoms and to cure various ailments, both acute and chronic. It was evaluated recently for its psychopharmacological activity in mice, revealing marked dose-dependent sedative effects on the central nervous system, 11,12) including protection against pentylenetetrazol, picrotoxin, and transcorneal electroshock-induced convulsion, and its hypnotic and hypothermic properties. 13) Furthermore, several recent reports have stated that linalool shows anti-proliferative activity against some solid tumor cells such as melanoma cells and renal cell adenocarcinoma cells 14) and HepG2.…”
mentioning
confidence: 99%